Political business cycle and fiscal discipline in Sub-Saharan Africa - Funsho Obakemi; Hammed Adesola Adebowale; Babatunde Nageri Yusuf; Timothy Terwase Nev (European Journal of Government and Economics (EJGE), 2021)
We tested the Political Business Cycle theory in Sub-Sahara Africa. To provide an empirical explanation for this nexus, this paper used unbalanced panel data from thirty-six (36) Sub-Saharan African countries between 1990 and 2018. The system Generalized Method of Moment (GMM) developed by Arrelano-Bover/Blundell-Bond was employed to analyze the collected data. The results of the system GMM revealed that the fiscal deficit is significantly large in election years and the deficit spending spills into the year after the election, though not as high as in the election year. We could not, however, find a significant effect in the pre-election year. In addition, we found evidence suggesting that though democracy significantly lowers the fiscal deficit, it promotes higher deficit spending in the election year and the year after the election. Hence, the study established the existence of a political business cycle in Sub-Saharan African countries. The study thus recommends that sound economic policies should be put in place to reduce the persistent deficit in SSA so as to maintain sustainable fiscal health, as well as the sustainability of macroeconomics, particularly enhanced industrialization, as the study found that countries' fiscal deficits are lower in more industrialized countries in the region.
Keywords: D72; H30; H60; 330; democracy; election; fiscal discipline; politics